Self Healing dengan Mindfulness Cooking pada Ibu Rumah Tangga di Desa Pasirtanjung. Kecamatan Tanjungsari, Kabupaten Bogor - Rosalinda, Irma; Hapsari, Iriani Indri; Yudhaningrum, Lupi (Universitas Negeri Jakarta, 2025)
Household chores are tasks performed daily, in a repetitive and routine manner. As a result, housewives may experience feelings of isolation and boredom. In some cases, these feelings can even become stressors for housewives. Furthermore, household work, which is mostly done at home, is often perceived as having little value because it lacks economic exchangeability. Consequently, many household responsibilities are considered trivial by others. A previous study indicated that career women or mothers who work outside the home tend to have better mental health compared to housewives. This is due to the monotonous nature of housework, which is primarily conducted within the home, indirectly creating psychological pressure on housewives. Over time, this pressure can impact their mental well-being. The Community Service Program of the Faculty of Psychology Education will focus on Self-Healing through Mindful Cooking for Housewives. This initiative involves housewives from Pasirtanjung Village, Tanjungsari, Bogor, as community partners who will participate in activities designed to cultivate focus and awareness while cooking. Through this practice, cooking can serve as a self-healing method to reduce stress and alleviate the exhaustion caused by repetitive and monotonous tasks. Numerous studies on mindfulness have highlighted its significant benefits for an individual’s psychological well-being.